Risk of Myocardial Infarction in Parents of HIV-infected Individuals:a population-based Cohort Study - Rasmussen, Line D; Omland, Lars H; Pedersen, Court; Gerstoft, Jan; Kronborg, Gitte; Jensen, Janne; Obel, Niels (BMC infectious diseases, 2010)
Background Previous studies have indicated an increased risk of myocardial infarction (MI) in HIV infected individuals especially after start of highly active antiretroviral therapy (HAART). It is however controversial whether the increased risk of atherosclerotic disease is exclusively associated with the HIV disease and HAART or whether life-style related or genetic factors also increase the risk in this population. To establish whether the increased risk of myocardial infarction in HIV patients partly reflects an increased risk of MI in their families, we estimated the relative risk of MI in parents of HIV-infected individuals. Methods From the Danish HIV Cohort Study and the Danish Civil Registration System we identified the parents of all HIV-infected patients born in Denmark after 1952 in whom a Danish born mother was identifiable. For each HIV patient, 4 matched population controls and their parents were identified. Cumulative incidence functions were constructed to illustrate time to first MI of the parents as registered in the Danish National Hospital Registry. Incidence rate ratios (IRR) were estimated by Cox's regression analyses. Due to the confidential type of the analysed data the study was approved by the Danish Data Protection Agency. Results 2,269 mothers and 2,022 fathers of HIV patients as well as 9,076 mothers and 8,460 fathers of control subjects were identified. We observed an increased risk of MI in mothers of HIV patients (adjusted IRR, 1.31; 95% CI: 1.08-1.60). The strongest association was seen in case the offspring was infected heterosexually (adjusted IRR, 1.59; 95% CI: 1.07-2.35) or by IV drug abuse (IVD) (adjusted IRR, 1.63; 95% CI: 1.02-2.60). In fathers of HIV patients the risk of MI was only increased if the offspring was infected by IVD (adjusted IRR, 1.42; 95% CI: 1.01-2.00). Conclusion Mothers of HIV-infected patients have an increased risk of MI. We presume that this stems from family related life style risk factors, some of which may also influence the risk of MI in HIV-infected patients.